SNP's and its correlation with hypertension: A comprehensive review - Manohar Murugan; Karthikeyan Ramalingam; M Nazzuredin; Hussain Ahmed Rashed; Ganesh Punamalai (Wolters Kluwer Medknow Publications, 2013)
Hypertension is a growing global problem, which mostly affects the adults. It is a risk factor for death from stroke, myocardial infarction, congestive heart failure, ischemic heart disease, peripheral vascular disease, and progressive renal damage. These diseases are responsible for considerable morbidity and high mortality rate. Human essential hypertension (EH) is a complex and multifactorial trait influenced by environmental and genetic determinants. Early detection of genetic predisposition in hypertensive patients will enable prompt treatment and avoidance of complications. The use of SNPs in genetic disease detection is facilitated by the recent discovery of more than 4 million SNPs in the human genome that have the potential to be a rich source of genetic markers to establish genetic linkage and as indicators of disease. Such genetic research will open the new frontiers in diagnosis and treatment of diseases like hypertension.